A escrita de relatos biográficos com base na pedagogia de gêneros de texto: ideação e avaliativiade na perspectiva sistêmico-funcional - Cecchin, Anidene de Siqueira (2021)
This thesis has as its general aim to analyze linguistic resources of the discursive systems of IDEATION and APPRAISAL that underline the instance of the biographical recount genre in texts produced by lower secondary education students during the dynamisation of the Teaching and Learning Cycle from Sydney School. Under the theoretical foundations of Systemic Functional Linguistics (HALLIDAY; MATTHIESSEN, 1999; 2004; 2014), with a focus on the discursive systems of IDEATION (MARTIN, 1992; MARTIN; ROSE, 2007) and APPRAISAL (MARTIN; WHITE, 2005), on the biographical recount genre assumptions (MARTIN; ROSE, 2008; CRHISTIE; DEREWIANKA, 2008) and based on the Genre Pedagogy (ROSE; MARTIN, 2012), a qualitative research, supported on exploratory and research-action methods, was developed. Through the exploratory study, it was possible to search for prototypical texts of the biographical recount genre on the Museu da Pessoa site, in order to model reading and writing activities of this text genre, in a textbook. The activities were dynamized in a research-action (THIOLLENT, 2011), performed in a teaching context, in the scope of Ateliê de Textos Extension Program (FUZER, 2016, 2021), considering the strategies of Deconstruction, Joint Construction, and Individual Construction of the Teaching and Learning Cycle (ROSE; MARTIN, 2012) and the strategies of diagnostic writing and socialization, used by Ateliê de Textos Program. With the purpose of investigating which linguistic resources of the discursive systems of IDEATION and APPRAISAL underline the instance of the biographical recount genre in texts produced by lower secondary (grade 9) education students, during the dynamisation of the Teaching and Learning Cycle from Sydney School, and of revealing learning, the diagnostic version, the version number 1, and the final version, produced by the students, were analyzed. The results showed the closeness to the biographical recount according to recurrences: Material and Relational processes to reveal actions of doing and meanings of being and of identifying for the one whose biography is about; circumstances of location, time and place, of accompaniment, and of cause, reason, to reveal temporal sequence for the activities, to indicate the place in which the events occurred, the participants who were involved, and the reasons for the behaviors and attitudes; relations of similarity by repetition and contrast by opposition of the subtype of converse and contrast by series of the subtype of cycles to construe the fields of experience in the texts and the social world of the person whose biography is about; appraisals of affect of the type of happiness and satisfaction, of judgment of the type of normality, capacity, and tenacity and of appreciation of the type of valuation for the one whose biography is about, his behavior, the things, and the people related to him. These results indicated progress in the students’ texts, the need to consider the path taken since the diagnostic to the final versions, the importance of the genre choice to be studied and the previous linguistic analysis by the teacher before working it in the classroom.